ON CHARACTERIZATION OF INVARIANT AND EXACT SOLUTIONS OF HUNTER-SAXON EQUATION - Korpinar, Zeliha; İnç, Mustafa (Editura Bibliotheca-Bibliotheca Publ House, 2018)
In this work, Lie symmetry analysis is applied on Lax's fifth-order KdV and Hunter-Saxton equations. By using point symmetry, all of the geometric vector fields of these equations are presented. Then, on the basis of the optimal system, similarity reductions and exact solutions are obtained.
Keywords: Lax's fifth-order KdV equation; Hunter-Saxton equation; Symmetry analysis; Exact solutions; Soliton